Differential methylation of microRNA encoding genes may contribute to high myopia - Swierkowska, Joanna; Vishweswaraiah, Sangeetha; Mrugacz, Malgorzata; Radhakrishna, Uppala; Gajecka, Marzena (Frontiers in Genetics, 2023)
High myopia (HM), an eye disorder with a refractive error ≤ -6.0 diopters, has multifactorial etiology with environmental and genetic factors involved. Recent studies confirm the impact of alterations in DNA methylation and microRNAs (miRNAs) on myopia. Here, we studied the combined aspects evaluating to the role of methylation of miRNA encoding genes in HM. From the genome-wide DNA methylation data of 18 Polish children with HM and 18 matched controls, we retrieved differentially methylated CG dinucleotides localized in miRNA encoding genes. Putative target genes of the highest-ranked miRNAs were obtained from the miRDB and included in overrepresentation analyses in the ConsensusPathDB. Expression of target genes was assessed using the RNA sequencing data of retinal ARPE-19 cell line. We identified differential methylation of CG dinucleotides in promoter regions of MIR3621, MIR34C, MIR423 (increased methylation level), and MIR1178, MIRLET7A2, MIR885, MIR548I3, MIR6854, MIR675, MIRLET7C, MIR99A (decreased methylation level) genes. Several targets of these miRNAs, e.g. GNAS, TRAM1, CTNNB1, EIF4B, TENM3 and RUNX were previously associated with myopia/HM/refractive error in Europeans in genome-wide association studies. Overrepresentation analyses of miRNAs’ targets revealed enrichment in pathways/processes related to eye structure/function, such as axon guidance, transcription, focal adhesion, and signaling pathways of TGF-β, insulin, MAPK and EGF-EGFR. Differential methylation of indicated miRNA encoding genes might influence their expression and contribute to HM pathogenesis via disrupted regulation of transcription of miRNAs’ target genes. Methylation of genes encoding miRNAs may be a new direction in research on both the mechanisms determining HM and non-invasive indicators in diagnostics.